m -Cresol methylation: Role of internal and external acid sites in the product distribution - Acevedo, Mauro Dino (2017)
The effect of the porous structure and the role of internal and external acid sites in product distribution in gas-phase alkylation of m-cresol with methanol were studied on zeolites HBEA, HZSM5 and HMCM22. Catalysts were characterized by N2 physisorption and FTIR of adsorbed pyridine. Trimethylated product formation was inhibited in narrower pore size zeolites (HMCM22 and HZSM5) and a preferential selectivity to smallest dimethylphenol isomer (2,5-dimethylphenol) was observed. The selectivity to 2,5-dimethylphenol on HMCM22 reached a value of 82% after suppressing the acid sites of the external cavities and pore mouth using 2,4-dimethylquinoline, which is a basic molecule too bulky to diffuse through the narrow pores of these zeolites.